Properties and effects of crosslinked polymer on starch and polyactic acid blend / Wang Ying - Wang, Ying (2018)
The blend of starch and PLA possessing the excellent properties of plastic products and its complete degradability has been a hot research topic in recent years. In the experiment, 7 experimental samples are made by applying the method of melting the blend of polylactic acid, starch and trimethylchlorosilane in different proportions and the mechanical properties, optical analysis and water absorption tests are conducted respectively. The changing trend of various properties of polylactic acid and starch at different mass ratios is analyzed as well as the influence of addition of trimethylchlorosilane on the properties of the composite. It is found that with the increase of starch content, the mechanical properties of the composites decreases (tensile strength, young modulus and elongation at break all decrease), the absorbability decreases and the water absorption increases. The FTIR analysis shows that the addition of trimethylchlorosilane does not substantially change the composition and structure of the blend system of starch / polylactic acid. The changes only occurred on several peak absorptions, which also leads to the changes in mechanical properties, adsorbability and absorbency.